Characterisation of the L-mode scrape off layer in MAST: decay lengths. (25th November 2015) - Militello, F.; Garzotti, L.; Harrison, J.; Omotani, J.T.; Scannell, R.; Allan, S.; Kirk, A.; Lupelli, I.; Thornton, A.J.
Abstract: This work presents a detailed characterisation of the MAST Scrape Off Layer in L-mode. Scans in line averaged density, plasma current and toroidal magnetic field were performed. A comprehensive and integrated study of the SOL was allowed by the use of a wide range of diagnostics. In agreement with previous results, an increase of the line averaged density induced a broadening of the midplane density profile. This increase was not correlated with divertor detachment, as confirmed by the systematic increase of the target ion flux and decrease of the emission. Also, no clear correlation is found with the density of the neutral particles at the wall. At comparable density levels, discharges with higher current did not show broadening. Outer target ion saturation current and heat flux decay lengths were measured and compared with midplane data. For the saturation current, the upstream projections of the target values, based on diffusive models, did not match the midplane measurements, neither in amplitude nor in trend, while agreement was found for the heat fluxes, suggesting a different perpendicular transport mechanism for the two channels. Furthermore, the value of the target heat flux decay length was quite insensitive to changes in the thermodynamic conditions, in agreement with recent scaling laws. In all the cases studied, sawtooth oscillations were present but they simply rescaled self-similarly the target profiles. The separatrix conditions changed significantly during a sawtooth cycle, but the target heat flux decay length and divertor spreading factor remained nearly constant, indicating that these quantities are rather insensitive to the upstream thermodynamic state of the SOL.